The role of the media in the professional education of future social workers - Konoshenko, Sergii (2021)
The article describes the role of the media in the professional education of future social workers. The influence of mass media in the professional education of a future social worker is represented - it is an opportunity for an individual to choose the information he wants to receive, and not what is imposed on him from outside, although this is due to certain technical and political difficulties; the use of reliable information flows for vocational education by taking into account the influence of various public organizations, cultural and educational activities. The influence of mass media in the professional training of future social workers has been developed, which includes internal and external factors influencing its components, inflows and outflows. Features of professional education of the future employee are characterized. The role of mass media in the activity of the future social worker is singled out. The role of mass media in the professional education of the future social worker is emphasized.